(untitled) (Perner’s Contacts, 2010)
The paper deals with motion and vital activity monitoring of person in the case of dangerous environment (rescue team member) or in the case of possible damage or injury threat (e.g. engine driver). Special attention is paid to modern INS MEMS components use.